Sikap Kontrol Diri dengan Perilaku Konsumtif Mahasiswa: Studi Empiris pada Mahasiswa FKIP Universitas Klabat - Merfin Hidayat; Aseng, Andrew Christian; Tumbel, Noldin Jerry; Pandeirot, Lanemey Brigitha (Jurnal Informatika Ekonomi Bisnis, 2023)
Self-control has an important role in people's lives, so studying its relationship with consumptive behavior is interesting. For this reason, this study was made to determine the level of self-control, the level of consumptive behavior, and the relationship between self-control and consumptive behavior, especially among students of the Faculty of Education at a private university in North Sulawesi. Quantitative and correlative research methods were used in this study with a total of 200 students as respondents. Furthermore, the mean value is used to find out the level of self-control and consumptive behavior. Meanwhile, the Pearson correlation test was used to seek out the relationship between self-control and consumptive behavior. The results obtained are (1) student self-control is in the high category or students agree that they can control themselves in shopping with an average value of 4.10; (2) student consumptive behavior is in the low category or students do not agree that they behave consumptively or consume goods excessively in shopping with an average value of 2.35, and (3) the results of data analysis using the Pearson correlation test showed that there is a strong and negatively significant relationship between self-control and consumptive behavior with a value of rxy = -0.360 and a significance value of p 0.000 <0.05. Thus, the higher the student's self-control, the lower the consumptive behavior.